What are the gaps in cardiovascular risk assessment and management in primary care for Māori and Pacific people in Aotearoa New Zealand? Protocol for a systematic review - Vanessa Selak; Matire Harwood; Shanthi Ameratunga; Corina Grey; Janine Paynter; Karen Marie Brewer; Julie Winter-Smith; Sandra Hanchard (BMJ Open)
Introduction In New Zealand, significant inequities exist between Māori and Pacific peoples compared with non-Māori, non-Pacific peoples in cardiovascular disease (CVD) risk factors, hospitalisations and management rates. This review will quantify and qualify already-reported gaps in CVD risk assessment and management in primary care for Māori and Pacific peoples compared with non-Māori/non-Pacific peoples in New Zealand.Methods and analysis We will conduct a systematic search of the following electronic databases and websites from 1 January 2000 to 31 December 2021: MEDLINE (OVID), EMBASE, Scopus, CINAHL Plus, NZresearch.org, National Library Catalogue (Te Puna), Index New Zealand (INNZ), Australia/New Zealand Reference Centre. In addition, we will search relevant websites such as the Ministry of Health and research organisations. Data sources will include published peer reviewed articles, reports and theses employing qualitative, quantitative and mixed methods.Two reviewers will independently screen the titles and abstracts of the citations and grade each as eligible, not eligible or might be eligible. Two reviewers will read each full report, with one medically qualified reviewer reading all reports and two other reviewers reading half each. The final list of included citations will be compiled from the results of the full report reading and agreed on by three reviewers. Data abstracted will include authors, title, year, study characteristics and participant characteristics. Data analysis and interpretation will involve critical inquiry and a strength-based approach that is inclusive of Māori and Pacific values. This means that critical appraisal includes an assessment of quality from an Indigenous perspective.Ethics and dissemination Ethical approval is not required. The findings will be published in a peer-reviewed journal and shared with stakeholders. This review contributes to a larger project which creates a Quality-Improvement Equity Roadmap to reduce barriers to Māori and Pacific peoples accessing evidence-based CVD care.